2004
DOI: 10.1111/j.0022-0477.2004.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Propagule pools mediate community assembly and diversity‐ecosystem regulation along a grassland productivity gradient

Abstract: Summary 1The relative importance of regional species pools and local ecological processes in governing landscape variation in plant species diversity and productivity was evaluated in a Kansas grassland. 2 We examined the impact of multispecies sowing treatments and experimental canopy disturbances on plant species diversity and ecosystem processes along a complex natural gradient of plant standing crop. 3 Data collected 4 years after sowing showed that plant invasion and diversity were seed limited in unprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
203
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(226 citation statements)
references
References 75 publications
20
203
1
2
Order By: Relevance
“…The most common empirical approach to questions of community-level effects of dispersal has been propagule addition experiments (Burke and Grime 1996;Tilman et al 1997;Stampfli and Zeiter 1999;Shurin 2000;Fargione et al 2003;Foster et al 2004;Mouquet et al 2004). A considerable number of such experiments, conducted across a wide range of habitats and community types, show that diversity of plant communities is often limited by dispersal; that is, when propagules are added, diversity is increased (reviewed by Turnbull et al 2000;Levine and Murrell 2003;Zobel and Kalamees 2005).…”
mentioning
confidence: 99%
“…The most common empirical approach to questions of community-level effects of dispersal has been propagule addition experiments (Burke and Grime 1996;Tilman et al 1997;Stampfli and Zeiter 1999;Shurin 2000;Fargione et al 2003;Foster et al 2004;Mouquet et al 2004). A considerable number of such experiments, conducted across a wide range of habitats and community types, show that diversity of plant communities is often limited by dispersal; that is, when propagules are added, diversity is increased (reviewed by Turnbull et al 2000;Levine and Murrell 2003;Zobel and Kalamees 2005).…”
mentioning
confidence: 99%
“…Most experimental studies of constructed species assemblages determined that increasing diversity contributes to greater biomass production (e.g., Hooper et al 2005, Spehn et al 2005. Alternatively, species reduction experiments in natural systems revealed biomass was resilient to decreased biodiversity , Suding et al 2006), while Foster et al (2004) demonstrated during species addition experiments that species pools or communities were integral to increased biomass. These experiments were comparatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Grassland and savanna plant communities, especially successional ones, often may be invasible and/or unsaturated with species (Tilman 1997, Foster et al 2004, Zeiter et al 2006. Community "invasibility" means that species whose propagules are added to the community establish populations.…”
Section: Introductionmentioning
confidence: 99%
“…Rigorous evaluations of seed limitation of plant population size, community invasibility and saturation are rare because few seed addition studies have been of sufficient duration to determine whether adding seed increases numbers of reproductive individuals of the added species (reviewed in Turnbull et al 2000). However, several long-term studies have documented sustained population increases and community responses to seed addition in grasslands and savannas (Foster and Tilman 2003, Foster et al 2004, Zeiter et al 2006. One of the striking and poorly explained results of seed addition experiments in herbaceous plant communities is the large variation among sites in the magnitude of population and community response to increased density and diversity of the seed rain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation